Optical µ-Printing of Cellular-Scale Microscaffold Arrays for 3D Cell Culture - Xia Ouyang (Nature Portfolio, 2017)
Abstract Guiding cell culture via engineering extracellular microenvironment has attracted tremendous attention due to its appealing potentials in the repair, maintenance, and development of tissues or even whole organs. However, conventional biofabrication technologies are usually less productive in fabricating microscale three-dimensional (3D) constructs because of the strident requirements in processing precision and complexity. Here we present an optical µ-printing technology to rapidly fabricate 3D microscaffold arrays for 3D cell culture and cell-scaffold interaction studies on a single chip. Arrays of 3D cubic microscaffolds with cubical sizes matching the single-cell size were fabricated to facilitate cell spreading on suspended microbeams so as to expose both apical and basal cell membranes. We further showed that the increasing of the cubical size of the microscaffolds led to enhanced spreading of the seeded human mesenchymal stem cells and activation of mechanosensing signaling, thereby promoting osteogenesis. Moreover, we demonstrated that the spatially selective modification of the surfaces of suspended beams with a bioactive coating (gelatin methacrylate) via an in-situ printing process allowed tailorable cell adhesion and spreading on the 3D microscaffolds.